A Case Study of Curriculum Implementation and K-13 Challenges in Indonesia - Nuraeni, Yeni; MS, Zulela; Boeriswati, Endry (International Journal for Educational and Vocational Studies, 2020)
The K-13 curriculum has been implemented since July 2013 in several Indonesian schools and might have been in effect in all school arround 2014. The study was aimed to obtain information regarding teachers difficulties in impelemnting the curriculum 2013. The research was descriptive explorative research by means of qualitative data gathering which conducted from July 2016 to January 2018. The data on teachers difficulties in implementing the curriculum 2013 were gathered by means of interviews, observation, and focus discussion with elementary school teachers and the vice principals of curriculum in Tangerang City Indonesia. The result of the study showed that in implementing the curriculum 2013 , the teachers had more difficulties the content standard 35.2%, the process standard 25.3%, the assessment standar 20.0%, The teacher and educational personal standar 4.2%, the infrastructure standard 4.2%, the management standard 4.2%,the graduate compotence standard 3.90%, and the funding standard 3.0%. The highest of them is the difficulty in understanding the implementation standard, the second on processes standards and third on assessment standards. This reseacrh is expected to lead to an outcome that will answer the needs of the community that the curriculum 2013 requires a lot of improvements and development so that all the problems found can be solved.